Biofouling of crypts of historical and architectural interest at La Plata Cemetery (Argentina) - Guiamet, Patricia Sandra (2012)
Cemeteries are part of the cultural heritage of urban communities, containing funerary crypts and monuments of historical and architectural interest. Efforts aimed at the conservation of these structures must target not only the abiotic stresses that cause their destruction, such as light and humidity, but also biofouling by biotic agents. The purpose of this study was to assess the development of biofouling of several historically and architecturally valuable crypts at La Plata Cemetery (Argentina). Samples obtained from the biofilms, lichens, and fungal colonies that had developed on the marble surfaces and cement mortar of these crypts were analyzed by conventional microbiological techniques and by scanning electron microscopy. The lichens were identified as Caloplaca austrocitrina, Lecanora albescens, Xanthoparmelia farinosa and Xanthoria candelaria, the fungi as Aspergillus sp., Penicillium sp., Fusarium sp., Candida sp. and Rhodotorula sp., and the bacteria as Bacillus sp. and Pseudomonas sp. The mechanisms by which these microorganisms cause the aesthetic and biochemical deterioration of the crypts are discussed. © 2011 Elsevier Masson SAS.